The Influence of The Snowball Throwing Learning Model on The Science Learning Outcomes of Grade 5 Students - Ewis Feronika Septiani Sipayung; Martua Reynhat Sitanggang Gusar; Kevin William Andri Siahaan; Theo Affany Dhea Purba; Uci Nursanty Haloho (Universitas Muhammadiyah Mataram, 2021)
The research objective was to determine the significant difference between student science learning outcomes taught through the Snowball Throwing model and students taught through conventional learning in class V SD Plus Tigabalata. The study population was all students in grade V SD Plus Tigabalata Jorlang Hataran totaling 65 students. Science learning outcomes data were collected using an instrument in the form of a regular multiple-choice test. The t-test is this data. The results showed that there was a significant difference between students who took the Snowball Throwing model learning and students who took conventional learning (that = 2,562> t table = 2,000) with DB = 82 (Σn-2 = 84-2 = 82) and the level of significance 5%. So it can be concluded that the Snowball Throwing model has a significant effect on the learning outcomes of SD Plus class V IPA students in Tigabalata, Jorlang Hataran District.